Human Resource Analytics Strategy to Optimize Digital Business Accounting Processes - SD, Surya Safari; Renaldo, Nicholas; Junaedi, Achmad Tavip; Suhardjo, Suhardjo; Panjaitan, Harry Patuan; Hutahuruk, Marice Br; Yovita, Indri; Cecilia, Cecilia; Wahid, Nabila; Veronica, Kristy (International Conference on Business Management and Accounting, 2025)
The study seeks to generate novel insights into how HR analytics can serve as a strategic lever, moving beyond conventional HR metrics to drive improvements in process performance, employee competencies, and organizational agility. The study seeks to generate novel insights into how HR analytics can serve as a strategic lever, moving beyond conventional HR metrics to drive improvements in process performance, employee competencies, and organizational agility. This study adopts a qualitative exploratory design to understand how organizations leverage Human Resource Analytics (HRA) to optimize digital business accounting processes. To address the novelty of exploring how HRA supports digital accounting (an under-researched link), this study will focus on cross-functional perspectives, collecting data from both HR and accounting leaders rather than HR alone. The findings reveal that when HRA is applied cross-functionally, it becomes a powerful enabler of digital transformation by identifying skill gaps, informing targeted training, and improving accounting process outcomes such as accuracy and efficiency. HR and Finance leaders should collaborate to embed HR analytics into transformation projects, ensuring that skill gaps are identified and addressed proactively.